Amyloids in solid-state nuclear magnetic resonance: potential causes of the usually low resolution - Espargaró A (Dove Medical Press, 2015)
Alba Espargaró, Maria Antònia Busquets, Joan Estelrich, Raimon Sabate Department of Physical Chemistry, School of Pharmacy, Institute of Nanoscience and Nanotechnology (IN2UB), University of Barcelona, Barcelona, Spain Abstract: Amyloids are non-crystalline and insoluble, which imply that the classical structural biology tools, ie, X-ray crystallography and solution nuclear magnetic resonance (NMR), are not suitable for their analysis. In the last years, solid-state NMR (ssNMR) has emerged as an alternative tool to decrypt the structural signatures of amyloid fibrils, providing major contributions to our understanding of molecular structures of amyloids such as β-amyloid peptide associated with Alzheimer’s disease or fungal prions, among others. Despite this, the wide majority of amyloid fibrils display low resolution by ssNMR. Usually, this low resolution has been attributed to a high disorder or polymorphism of the fibrils, suggesting the existence of diverse elementary β-sheet structures. Here, we propose that a single β-sheet structure could be responsible for the broadening of the line widths in the ssNMR spectra. Although the fibrils and fibers consist of a single elementary structure, the angle of twist of each individual fibril in the mature fiber depends on the number of individual fibrils as well as the fibril arrangement in the final mature fiber. Thus, a wide range of angles of twist could be observed in the same amyloid sample. These twist variations involve changes in amino acid alignments that could be enough to limit the ssNMR resolution. Keywords: amyloid, fibril, misfolding, β-structure, ssNMR, NMR, β-sheet